Pengembangan Multimedia Interaktif Berbasis Website Pada Materi Peluang - Rahman Patingki; Sarson W. Pomalato; Novianita Achmad (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to produce interactive multimedia on opportunity material for class VIII Even Semester Junior High Schools. This research uses the Research and Development (R&D) research methodology. This development research follows the four-D development model. The Thiagarajan, Semmel and Semmel models consist of four stages, namely Define, Design, Develop and Disseminate. The validation results obtained from 3 media experts and 3 material experts were 84.03% and 89% with the criteria "Very Valid for Use". The suitability of the media was obtained through the results of a media readability test by 5 class VIII students at SMP Muh 2 Gorontalo, amounting to 83.67%, with the criteria "Very Suitable for Use". The practicality of the media was obtained through a response questionnaire from students and mathematics teachers at SMP Muh 2 Gorontalo towards interactive multimedia based on website. The results of the response questionnaire for class VIII students at Muh 2 Gorontalo Middle School were 91.7%, the results of the response questionnaire for mathematics teachers at Muh 2 Gorontalo Middle School were 89.47%, with the criteria "Very Practical to Use". The conclusion is that interactive multimedia is based website valid, feasible, and practical to use in class VIII opportunity material.